Impact of Obesity-Related Endoplasmic Reticulum Stress on Cancer and Associated Molecular Targets - Joud AlBashtawi; Hend Al-Jaber; Sara Ahmed; Layla Al-Mansoori (Biomedicines, 2024)
Obesity, characterized by excessive body fat, is closely linked to endoplasmic reticulum (ER) stress, leading to insulin resistance and type 2 diabetes. Inflammatory pathways like c-Jun N-terminal kinase (JNK) worsen insulin resistance, impacting insulin signaling. Moreover, ER stress plays a substantial role in cancer, influencing tumor cell survival and growth by releasing factors like vascular endothelial growth factor (VEGF). The unfolded protein response (UPR) is pivotal in this process, offering both pro-survival and apoptotic pathways. This review offers an extensive exploration of the sophisticated connection between ER stress provoked by obesity and its role in both the onset and advancement of cancer. It delves into the intricate interplay between oncogenic signaling and the pathways associated with ER stress in individuals who are obese. Furthermore, this review sheds light on potential therapeutic strategies aimed at managing ER stress induced by obesity, with a focus on addressing cancer initiation and progression. The potential to alleviate ER stress through therapeutic interventions, which may encompass the use of small molecules, FDA-approved medications, and gene therapy, holds great promise. A more in-depth examination of pathways such as UPR, ER-associated protein degradation (ERAD), autophagy, and epigenetic regulation has the potential to uncover innovative therapeutic approaches and the identification of predictive biomarkers.